Affirmative Action: One Size Does Not Fit All - Kala Krishna; Alexander Tarasov (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
This paper identifies a new reason for giving preferences to the disadvantaged using a model of contests. There are two forces at work: the effort effect working against giving preferences and the selection effect working for them. When education is costly and easy to obtain (as in the U.S.), the selection effect dominates. When education is heavily subsidized and limited in supply (as in India), preferences are welfare reducing. The model also shows that unequal treatment of identical agents can be welfare improving, providing insights into when the counterintuitive policy of rationing educational access to some subgroups is welfare improving.
urn:nbn:de:bvb:19-epub-17196-3
Keywords: D61; I23; 330; contests; educational quotas; private benefits; social welfare; Antidiskriminierungsrecht; Bildungspolitik; Minderheit; Subvention; Schulbesuch; Schulauswahl; Theorie; USA; Indien